Unmet service needs evaluated by case managers among disabled patients on hemodialysis in Japan - Sugisawa H (International Journal of Nephrology and Renovascular Disease, 2018)
Hidehiro Sugisawa,1 Toshio Shinoda,2 Yumiko Shimizu,3 Tamaki Kumagai,4 Hiroaki Sugisaki,5 Seiji Ohira6,† 1Department of Gerontology, Graduate School of Gerontology, J. F. Oberlin University, Tokyo, 2Department of Medical Care Technology, Faculty of Medical and Health Science, Tsukuba International University, Tsuchiura, 3Department of Community Health Nursing, The Jikei University School of Nursing, Chofu, 4Department of Fundamental Nursing, Graduate School of Nursing, Osaka City University, Osaka, 5Hachioji Azumacho Clinic, Hachioji, Tokyo, 6Sapporo Kita Clinic, Sapporo, Hokkai-do, Japan †Professor Dr. Seiji Ohira passed away on September 5, 2017 Background: This study aimed to investigate the levels of unmet needs for home and community-based services (HCBS) evaluated by case managers (CMs) among disabled patients on hemodialysis (DPHD) and to examine factors related to unmet needs. Unmet needs for HCBS were defined as situations in which patients do not use or underuse HCBS despite needing them. Candidates for the factors relating to unmet needs for HCBS included three dimensions: predisposing, enabling, and need factors.Methods: Self-administrated questionnaires were collected from 391 CMs of DPHD certified with long-term care insurance. These were introduced by the dialysis facilities that a member of the Japanese Association of Dialysis Physicians belonged to. CMs were asked questions about their management of each individual case. HCBS included home help, visiting nursing, daycare, and short stay.Results: The prevalence of unmet needs for each HCBS ranged from 32% for home help to 48% for short stay. Barriers to service usage in the patients were associated with unmet needs for all four services. The patients with more severe cognitive malfunction were more likely to have unmet needs for visiting nursing and short stay. Heavier burden with caregiving was associated with more likelihood of unmet needs for home help and short stay.Conclusion: CMs need to monitor unmet needs after coordinating HCBS for DPHD and need to encourage HBCS use among patients with impaired cognitive function and caregivers with heavier caregiving burdens. Keywords: disabled hemodialysis patients, long-term care, home and community-based services, Andersen’s behavioral model, barriers to service usage, Japan